Penerapan Teknologi Kesehatan Tepat Guna di Era Industri 4.0 dalam Perlindungan Anggrek Alam Terhadap Infeksi Penyakit di Kebun Raya - Mahfut Mahfut; Yunda Heningtyas; Sukimin (Jurnal SOLMA, 2021)
The existence of native orchids in the Liwa Botanical Garden is one of the wealth of native flora of Southern Sumatra that needs to be preserved. Based on the identification results, it is known that some individual orchids show symptoms of virus infection. The aim of this research is to find the appropriate, effective, and efficient method of controlling viral diseases. The method used is through the approach of several scientific fields such as biology, plant protection, and computer science. The application of endophytic mycorrhizal bio-agent resistance induction as a biocontrol agent capable of suppressing viral disease replication in plants can be used as a cheap and environmentally friendly method compared to pesticides. In addition, the use of an expert system method for diagnosing plant diseases with a web-based case-base reasoning method. This service is important considering that the botanical gardens do not know the safe and environmentally friendly methods of controlling disease in orchids. This activity is a vehicle for sharing good knowledge between the service team and the manager of the Liwa Botanical Garden. With the development of this method, it is hoped that the detection process of controlling viral diseases in natural orchids will be more accurate and faster.